2020
DOI: 10.1007/s11469-020-00358-1
|View full text |Cite
|
Sign up to set email alerts
|

Online Gaming During the COVID-19 Pandemic in India: Strategies for Work-Life Balance

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic has brought the entire world to a relative standstill, affecting millions worldwide at the time of writing (June 24, 2020) (World Health Organization [WHO] 2020). With the absence of an effective vaccine, public health measures have been implemented by governments worldwide, such as quarantine, closing workplaces (including schools and businesses), and spatial distancing (Nussbaumer-Streit et al. 2020). To combat the spread of COVID-19, the Indian governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 35 publications
1
78
3
3
Order By: Relevance
“…These points should be considered in prevention and intervention approaches in order to help individuals adapt their health behaviors. Several guidelines have been developed recently, providing advices on how to manage excessive behaviors (i.e., screen use) during the COVID-19 pandemic [e.g., ( 12 , 40 )] and to prevent and treat addictive behavior-related disorders ( 38 ). Still, the current study calls for targeted preventions and interventions toward particularly vulnerable individuals (i.e., between-person relationships regarding sex, age, and living alone).…”
Section: Discussionmentioning
confidence: 99%
“…These points should be considered in prevention and intervention approaches in order to help individuals adapt their health behaviors. Several guidelines have been developed recently, providing advices on how to manage excessive behaviors (i.e., screen use) during the COVID-19 pandemic [e.g., ( 12 , 40 )] and to prevent and treat addictive behavior-related disorders ( 38 ). Still, the current study calls for targeted preventions and interventions toward particularly vulnerable individuals (i.e., between-person relationships regarding sex, age, and living alone).…”
Section: Discussionmentioning
confidence: 99%
“…In lieu to time saved from not having to commute, some started work earlier but ended at their habitual time 59 . Outside work, online gaming platforms and social media activity also increased 60 (3) Sleep quality measures were not obtained, which could be affected by anxiety from the impending loss of jobs or contracting the disease. However, one study showed unchanged or even improved sleep quality during the lockdown, particularly once shift workers and individuals who showed symptoms of COVID-19 were excluded from the analyses 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In lieu to time saved from not having to commute, some started work earlier but ended at their habitual time 59 . Outside work, online gaming platforms and social media activity also increased 60 . Facebook reported increases of 100% on voice over internet calls and 50% in text messages on WhatsApp, Facebook Messenger and Instagram platforms during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In lieu to time saved from not having to commute, some started work earlier but ended at their habitual time 59 . Outside work, online gaming platforms and social media activity also increased 60 While this study highlights strengths of being able to rapidly and remotely assess the impact of various intervention policies on sleep and resting heart rate, there are a few limitations to consider. (1) Only sleep periods between 4-12 hours were analyzed.…”
Section: Discussionmentioning
confidence: 99%